Rancang Bangun Sistem Informasi Rekam Medis Santri Terintegrasi Berbasis Web Menggunakan CodeIgniter 4 - Muflihatul Hasanah; Firman Santoso (Jurnal Ilmiah Teknik Informatika (TEKINFO), 2026)
The Health Services at the Salafiyah Syafi'iyah Sukorejo Islamic Boarding School havecurrently implemented an electronic medical record (EMR) system. However, in its execution, thesystem requires further development as it is not yet perfectly integrated across service units. Theseparation of data access between the Boys' Satellite Clinic and the Girls' Satellite Clinic causesoperational barriers since staff at the Central Clinic must manage data through different platforms,leading to administrative inefficiencies in student referral times and non-real-time datasynchronization. Furthermore, the current system lacks automated data interconnection fromregistration to the doctor's unit and requires improvements in access rights management andactivity logs. To address these issues, a web-based integrated EMR platform was developed usingthe CodeIgniter 4 framework, consolidating all service units into a single unified interface basedon the Student Identification Number (NIS). NIS is utilized as the primary search parameter due toits unique nature (primary key) to anticipate the high probability of identical names amongthousands of students, thereby preventing the risk of interchanged medical records. The systemP-ISSN: 1411-3635E-ISSN: 2962-5645journals.upi-yai.ac.id/index.php/TEKINFO/issue/archive10 TEKINFO VOL. 27, NO. 1 , April 2026development follows the Waterfall method. The testing results indicate that the developed systemsuccessfully unifies data access from satellite units to the central unit, automates registration-todoctordata flows, and provides referral notification features before students arrive at the CentralClinic. The implementation of the Model-View-Controller (MVC) architecture in CodeIgniter 4 isproven to deliver a responsive web application execution performance and simplifies centralized,secure, and accurate student medical record data management.